Role of Cutaneous Aquaporins in the Development of Xeroderma in Type 2 Diabetes - Nobutomo Ikarashi; Nanaho Mizukami; Chenchen Pei; Ryogo Uchino; Izumi Fujisawa; Natsuko Fukuda; Risako Kon; Hiroyasu Sakai; Junzo Kamei (Biomedicines, 2021)
Xeroderma is induced by diabetes, reducing patients’ quality of life. We aimed to clarify the roles of cutaneous water channel aquaporin-3 (AQP3) in diabetic xeroderma using type 2 diabetes model db/db mice. Blood glucose levels were unchanged in 5-week-old db/db mice compared to db/+ mice (control mice), but the pathophysiology of type 2 diabetes was confirmed in 12-week-old db/db mice. The dermal water content and AQP3 expression in 5-week-old db/db mice were almost the same as those in the control mice. On the other hand, in 12-week-old db/db mice, the dermal water content and AQP3 expression were significantly decreased. The addition of glucose to HaCaT cells had no effect on AQP3, but tumor necrosis factor-α (TNF-α) decreased the AQP3 expression level. Blood TNF-α levels or skin inflammation markers in the 12-week-old db/db mice were significantly higher than those in control mice. AQP3 levels in the skin were decreased in type 2 diabetes, and this decrease in AQP3 may be one of the causes of xeroderma. Therefore, a substance that increases AQP3 may be useful for improving xeroderma. Additionally, a decrease in skin AQP3 may be triggered by inflammation. Therefore, anti-inflammatory drugs may be effective as new therapeutic agents for diabetic xerosis.